A new strategy of carbon – Pb composite as a bipolar plate material for unitized regenerative fuel cell system. (20th September 2021) - Thangarasu, Sadhasivam; Jung, Ho-Young; Wee, Jae-Hyung; Kim, Yoong Ahm; Roh, Sung-Hee
Abstract: In this study, we investigated the possibilities and combination of cost-effective materials of carbon (C) and lead (Pb) with polypropylene (PP) polymer as a new kind of bipolar plate for unitized regenerative fuel cell and polymer electrolyte membrane fuel cell systems. The homogeneous composite structure of C:Pb developed through facile mechanical milling process, and optimized. The new bipolar plate was fabricated with PP using compression molding process with hot pressing techniques. A dense and smooth surface morphology of C:Pb bipolar plate was acquired with the uniform thickness of 1.33 (±0.17) mm. Compared to C, an improved electrical properties (~20%) obtained to the powdered C:Pb composite materials because of homogeneous composition of Pb metal particles with large surface area of C. The C:Pb bipolar plate revealed an efficient water contact angle behavior than the C bipolar plate, where the water contact angle for C and C:Pb bipolar plates are 82.4° and 93.1°, respectively. A sophisticated electrochemical stability performance has obtained to the C:Pb bipolar plate in acidic condition. According to Tafel plots analysis, higher corrosion resistance has observed to the C:Pb bipolar plate than the C bipolar plate. The fabricated new kind of C:Pb bipolar plate provides the many advantageous, thus it proves the insights for further developments and applicability in the practical application. In the perspective view, the performances of C:Pb bipolar plate can be further altered through modification of different carbon structures together with impregnation of Pb nanostructured materials into the pores and/or embedded throughout the surface, and efficient conductive polymers.